SIKAP BAHASA REMAJA: KASUS PEMAKAIAN BAHASA INDONESIA DALAM RUBRIK “DETEKSI” JAWA POS - Foriyani Subiyatningsih (Balai Bahasa Provinsi Riau, 2016)
Teenagers language is considered as variant of Indonesian language which socially mark that the social group who uses such language are teenagers. In various contexts, the using of teenagers language shows different forms. The using of Indonesian language in rubric “Deteksi” Jawa Pos brings particularity, syntactic, and lexicon level. This article aims to describe the language attitude of teenagers with using not standardized indicator of Indonesian language in rubric “Deteksi” Jawa Pos. The data in this research is in using Indonesian language in the forms of words, phrases and sentences. The method used in thisresearch is qualitative method. Data collection was conducted by using observation method and taking note technique. The data analyzing applied distributional method. The research result shows that (1) there are some not- standardized indicators in rubric “Deteksi” Jawa Pos such as interferences, code mixing, and unexamined spelling in writing forms and (2) teenegers language attitude in term of the awareness of language norm.